HylA, an Alternative Hydrolase for Initiation of Catabolism of the Phenylurea Herbicide Linuron in Variovorax sp. Strains - Bers, K. (American Society for Microbiology, 2013)
Variovorax sp. strain WDL1, which mineralizes the phenylurea herbicide linuron, expresses a novel linuron-hydrolyzing enzyme, HylA, that converts linuron to 3,4-dichloroaniline (DCA). The enzyme is distinct from the linuron hydrolase LibA enzyme recently identified in other linuron-mineralizing Variovorax strains and from phenylurea-hydrolyzing enzymes (PuhA, PuhB) found in Gram-positive bacteria. The dimeric enzyme belongs to a separate family of hydrolases and differs in K(m), temperature optimum, and phenylurea herbicide substrate range. Within the metal-dependent amidohydrolase superfamily, HylA and PuhA/PuhB belong to two distinct protein families, while LibA is a member of the unrelated amidase signature family. The hylA gene was identified in a draft genome sequence of strain WDL1. The involvement of hylA in linuron degradation by strain WDL1 is inferred from its absence in spontaneous WDL1 mutants defective in linuron hydrolysis and its presence in linuron-degrading Variovorax strains that lack libA. In strain WDL1, the hylA gene is combined with catabolic gene modules encoding the downstream pathways for DCA degradation, which are very similar to those present in Variovorax sp. SRS16, which contains libA. Our results show that the expansion of a DCA catabolic pathway toward linuron degradation in Variovorax can involve different but isofunctional linuron hydrolysis genes encoding proteins that belong to evolutionary unrelated hydrolase families. This may be explained by divergent evolution and the independent acquisition of the corresponding genetic modules.